Team Interdependence as a Substitute for Empowering Leadership Contribution to Team Meaningfulness and Performance - Lisak, Alon; Harush, Raveh; Icekson, Tamar; Harel, Sharon (Frontiers in Psychology, 2022)
This study uses a relational work design perspective to explore substitutes for leadership behaviors that promote team meaningfulness and performance. We propose that team task interdependence, a structural feature facilitating interaction among team members, can be a substitute for the contributions of empowering leadership. Data were collected from 47 R&D and technology implementation teams across three organizations in a cross-sectional field study. The results revealed that high task interdependence attenuated the contributions of empowering leadership concerning team meaningfulness and, indirectly, to team performance. These findings highlight that the importance of leaders as generators of team meaningfulness is contingent on team relational work design.